2014
DOI: 10.1021/jm500348z
|View full text |Cite
|
Sign up to set email alerts
|

Propylene Cross-Bridged Macrocyclic Bifunctional Chelator: A New Design for Facile Bioconjugation and Robust 64Cu Complex Stability

Abstract: The first macrocyclic bifunctional chelator incorporating propylene cross-bridge was efficiently synthesized from cyclam in seven steps. After the introduction of an extra functional group for facile conjugation onto the propylene cross-bridge, the two carboxylic acid pendants could contribute to strong coordination of Cu(II) ions, leading to a robust Cu complex. The cyclic RGD peptide conjugate of PCB-TE2A-NCS was prepared and successfully radiolabeled with (64)Cu ion. The radiolabeled peptide conjugate was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 35 publications
(101 reference statements)
1
32
0
Order By: Relevance
“…NMR spectra were recorded using a JEOL JNM-LA400 FT NMR spectrometer (Tokyo, Japan) at a frequency of 400 MHz for 1 H spectra and 100 MHz for 13 C spectra. Liquid chromatography mass spectrometry was performed using an Agilent 1260 Infinity LC system (Santa Clara, CA, USA).…”
Section: General Methods and Physical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectra were recorded using a JEOL JNM-LA400 FT NMR spectrometer (Tokyo, Japan) at a frequency of 400 MHz for 1 H spectra and 100 MHz for 13 C spectra. Liquid chromatography mass spectrometry was performed using an Agilent 1260 Infinity LC system (Santa Clara, CA, USA).…”
Section: General Methods and Physical Measurementsmentioning
confidence: 99%
“…Crucially, the ligand should meet the required coordination demand of the metal ion in question in order to maximise stability. Another role of the pendent arm may be to provide an attachment point for a biomolecule to direct the resulting complex towards a certain bio-marker [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown these chelates to be also unstable in vivo. Their demetallation leads to the release and circulation of free copper ions, which generate undesired background noise in PET imaging. , To address the demetallation issue, we have developed a new category of propylene cross-bridged TE2A (PCB-TE2A) chelators that form ultra-stable copper­(II) complexes. , However, the cross-bridged chelators only form complexes with copper ions at high temperatures (>80 °C). ,, Thus, their application to radiolabeling a heat-sensitive antibody has not been achieved so far.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 To address the demetallation issue, we have developed a new category of propylene cross-bridged TE2A (PCB-TE2A) chelators that form ultra-stable copper(II) complexes. 12,23 However, the cross-bridged chelators only form complexes with copper ions at high temperatures (>80 °C). 12,23,24 Thus, their application to radiolabeling a heat-sensitive antibody has not been achieved so far.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There has been considerable interest in the synthesis and coordination chemistry of polyazacycles with coordinating pendant arms because of their potential use in applications such as magnetic resonance imaging (MRI) contrast agents [1,2], positron emission tomography (PET) [3,4], luminescence probes [5,6,7,8], catalysis [9], and so on. Among the polyazacycle derivatives, tetraazamacrocycles with acetate side chains have received the most attention owing to their strong chelating properties and higher selectivity toward di- or trivalent metal ions [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%